Adult Lymphoma / Leukemia T: Prevalent entity in South America - Beltran, Brady E. (2020)
Adult T - lymphoma / leukemia is an aggressive T lymphoproliferative entity associated retrovirus HTLV-1- T.HTLV-1 infection is endemic in Japan, the Caribbean, Africa, South America, and the Middle East. In South America, we have Peru, Brazil, Colombia and Chile.Peru is endemic for this virus. The prevalence of retroviruses in Europe and the USA. USA It is less than 1% but in Peru it is estimated that around 3% of the healthy adult population is a carrier of the retrovirus.From Chile, there have been several ATLL reports since 1992 by Dra. Cabrera et al.